Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Aktivitas Belajar Siswa pada Mata Pelajaran Ekonomi - Dewi Wahyuni; Inanna Inanna; Marhawati Marhawati; Muhammad Hasan; Rahmatullah Rahmatullah (Indonesian Journal of Social and Educational Studies, 2020)
The aim of this research is to increase the learning activities of student in economics subjects with the potentional for management of class X MIPA 3 Contry 3 Pangkep. This research is a classroom action research model conducted intwo cycles because it has reached an indicator of the success of the action. Indicator of the success of this study amounted to 75% positive activity, less than 20% negative activity. The subjects of this study were students of class X MIPA 3 in SMA Country 3 Pangkep in the academy year 2019/2020 which amounted to 32 students. Data collection techniques in this study used observers, interviews and documentations. Research show that the application of the learning mod based learning can increase student learning activities by 51% in cycle I and 76% in cycle II.